47‐4: Aging Behaviors of QLED with Different Structures. Issue 1 (29th May 2019) - Chen, Zinan; Qin, Zhiyuan; Zhou, Xinyi; Long, Jingwei; Chen, Shuming
Abstract : Quantum dot light‐emitting diodes (QLEDs) are recognized as one of the candidates for the development of next generation displays. However the stability issue restricts their industrialization. In this work, we investigated the aging behaviors of QLEDs with different structures. We identified that the lifetime of QLEDs is greatly affected by the hole transport layer (HTL). In addition, we found that devices encapsulated with and without desiccant exhibit different aging behaviors. The use of desiccant improved the stability of the HTL, but the positive aging which could prolong the lifetime of devices was alleviated. On the other hand, device without desiccant exhibited positive aging behavior but the HTL was degraded rapidly. It is concluded that there is a trade‐off between positive aging and stability of HTL.